Programs of Access to Pedagogy: Diagnostic of Its Design in Chilean Private Universities - Karen Núñez-Valdés; Neliot Villena Olivares; Cristian Villegas Dianta; Marisol López Núñez; Antonio Castillo-Paredes (MDPI AG, 2022)
The objective of this study is to describe and analyze comparatively the Programs of Access to Pedagogies (PAP) of Chilean private universities, in order to know how this policy has been developed in this type of institution. After an exhaustive and meticulous treatment of the information contained in the 11 private university programs in Chile, categories were created for later analysis, based on the criteria contained in the programs. The results were analyzed based on pre-established analytical criteria, within which three to seven categories were found that allow the description and analysis of the PAPs. Among these, categories related to "Development of skills", "Pedagogical vocation", "Promotion of equity", "Academic performance", "Transversal skills" and "Academic support" stand out, being found in eight programs of the 11 analyzed. Although the Programs of Access to Pedagogy careers, established objectives, eligibility criteria, permanence criteria, camping, among others, follow the law, these programs have limitations, due to their heterogeneous construction, which translates into the interpretation of the laws, for which a series of challenges emerge, all of them associated with the search for strategies to strengthen the attraction and training of future good teachers.